Fish Parasites (Labeo rohita and Schizothorax niger) of Jammu and Kashmir in India - Mukesh Mehta Ambani (Advances in Aquaculture and Fisheries Management, 2014)
The present study has been carried out to find out the parasites of Schizothorax niger and Labeo rohita during different months of the year 2013 to 2014. Parasites belonging to two groups viz. ciliophoran (Chilodonella) and crustacean (Argulus) were recorded from 200 fishes of Rohu (L. rohita) and S. niger collected from different parts of Jammu and Kashmir. These two parasites belong to Ectoparasitic group and no other parasite was recorded in the present study. The highest prevalence (60%) of infection has been recorded in ciliophorans and the lowest was in crustacean (48%). It was observed that highest parasitic prevalence (54%) was recorded during winter season (December-February) while the lowest prevalence (0%) recorded during rainy season (June-August). Cyprinid fish S. niger infested with ciliophoran had no pathogenic signs and the clinical signs were represented as increase of mucus laden masses on the surface of gills. No pathogenic signs were seen in L. rohita infested with Crustacean parasite and clinical signs were represented as gasping air, pale skin color, sluggish swimming, increase of mucus production and floating on surface often causes mortality. This is first report of protozoan parasites from fishes of Jammu and Kashmir.